2016
DOI: 10.3389/fcvm.2016.00023
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Integrative Physiological Effects of Isoflurane Anesthesia: The Paradigm of Cardiovascular Studies in Rodents using Magnetic Resonance Imaging

Abstract: To-this-date, the exact molecular, cellular, and integrative physiological mechanisms of anesthesia remain largely unknown. Published evidence indicates that anesthetic effects are multifocal and occur in a time-dependent and coordinated manner, mediated via central, local, and peripheral pathways. Their effects can be modulated by a range of variables, and their elicited end-effect on the integrative physiological response is highly variable. This review summarizes the major cellular and molecular sites of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 110 publications
(137 reference statements)
4
38
0
Order By: Relevance
“…17 With the use of N 2 O, it is possible to reduce the administered dose of the primary (volatile agent) and thus minimize its side effects. 18,19 The use of N 2 O in conjunction with isoflurane has led to higher and less variable values of blood pressure and heart rate and thus more stable physiological status than isoflurane alone when used in mice. 20 In addition, previous studies that investigated TCA rates under different anesthesias with conventional 13 general anesthesia 22 and not affecting the entropy of EEG, 23 it is expected to have a small effect on brain metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…17 With the use of N 2 O, it is possible to reduce the administered dose of the primary (volatile agent) and thus minimize its side effects. 18,19 The use of N 2 O in conjunction with isoflurane has led to higher and less variable values of blood pressure and heart rate and thus more stable physiological status than isoflurane alone when used in mice. 20 In addition, previous studies that investigated TCA rates under different anesthesias with conventional 13 general anesthesia 22 and not affecting the entropy of EEG, 23 it is expected to have a small effect on brain metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Some aspects of volatile anesthetics action have also been tested in other animal models, such as cats and horses, where it was shown that anesthetics can affect the function of many different ion channels and receptors, but rodents represent one of the most widely used model for the study of molecular and integrative physiological effects of isoflurane anesthesia (35). …”
Section: Discussionmentioning
confidence: 99%
“…The increased quantities are compensated by a reduction in HR, resulting in no significant changes in CO. The measured constant EF under high isoflurane dose, in combination with reduced afterload reported in the literature (isoflurane is a potent vasodilator), suggests a decrease in cardiac work. In addition, the significantly lowered HR reduces cardiac power output even further.…”
Section: Discussionmentioning
confidence: 99%
“…Isoflurane is the most commonly used anesthetic nowadays . In a typical setting, the depth of anesthesia is adjusted on the basis of the heart rate (HR) and rate of breathing .…”
Section: Introductionmentioning
confidence: 99%